Conocimientos de los estudiantes de enfermería sobre los cuidados generales de las heridas (Estima – Brazilian Journal of Enterostomal Therapy, 2023)
Objective: To evaluate nursing students' knowledge about general wound care. Methods: This is a research of quantitative approach, conducted with students in the final year of the undergraduate nursing course in higher education institutions in the region of Cariri, Ceará. Data collection was developed from the sampling technique "Snowball sampling", the data were tabulated in Microsoft Excel spreadsheet and subsequently analyzed. The study was approved by the Research Ethics Committee, according to the opinion of No. 4,112,506. Results: The research was conducted with 211 Nursing students who responded favorably to the questionnaire with questions regarding sociodemographic factors, sources of knowledge, knowledge of practice, knowledge regarding the care of patients with wounds. Conclusion: The interviewed students have considerable knowledge about general wound care.